Engineering considerations for lift-slab construction - Zallen, Ruben M.; Peraza, David B.; Technical Council on Forensic Engineering (American Society of Civil Engineers). (Reston, Virginia American Society of Civil Engineers, 2004)
"In 1987, the collapse of L'Ambiance Plaza in Bridgeport, Connecticut demonstrated the need to re-evaluate the engineering of lift-slab construction and determine what is needed to make it safe. This re-evaluation was made by the Task Committee on Lift-Slab Construction of the Technical Council on Forensic Engineering of the American Society of Civil Engineers." "Engineering Considerations for Lift-Slab Construction is based on the work of the task committee; it addresses engineering requirements for lift-slab construction and presents recommendations to engineers, architects, and lift-slab contractors for its safe use."--BOOK JACKET.
Based on a task committee report from the Technical Council on Forensic Engineering of ASCE.
Includes bibliographical references and index.
Keywords: Concrete construction; Concrete slabs; Electronic books